Distraction Osteogenesis of Severely Resorbed Mandible - Salah Sakka; Ali Al Rafedah; Nasser Alqhtani; Adel Alenazi (Hindawi Limited, 2022)
Edentulous patients require an adequate rehabilitation so that the alveolar ridge in the interforaminal region be restored for subsequent implant-supported overdentures. The ultimate goal of distraction is to reconstruct the alveolar ridge to a suitable height and width compatible with Atwood class 2 in an appropriate direction allowing the sagittal interalveolar relation to be normally restored. Methods. A 65-year-old man presented with a grade 4 Mandibular atrophy as per Atwood classification which resulted in unsatisfactory treatment with full dentures. Endo-Distractor Krenkel® device was used for anterior mandibular vertical distraction osteogenesis. Four mandibular implants (ITI Straumann, Basel, Switzerland) measuring diameter Ø=4.1 mm and length L=16 mm were inserted after the required retention period. Standardized prosthetic treatment was completed with titanium bar retained over dentures. Results. A distraction of 11 mm was achieved within 18 days followed by a retention period of 4 months. No signs of infection nor distractor anchorage loosening were detected, and minimal lingual tilting has occurred. Conclusion. Distraction is possible on severely atrophic mandibles. The quality of bone reconstruction is satisfactory for both functional and esthetic results.